1987
DOI: 10.1016/0165-0327(87)90017-6
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blockers in anxiety disorders

Abstract: Studies evaluating the antianxiety and antipanic properties of beta-blockers do not support their routine use in treating either generalized anxiety disorder or panic disorder. The use of propranolol for anxiety disorders accompanied by physical symptoms, especially cardiovascular complaints, may be effective in some patients when combined with benzodiazepines or perhaps in some non-responders to conventional treatment. Better designed studies are needed to evaluate the exact role of beta-blocking agents in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 40 publications
(67 reference statements)
2
26
1
Order By: Relevance
“…This has not been described clinically, although there have been reports that propranolol can produce depression (Hayes and Schulz, 1987). Nevertheless, the different explanations proposed for the present results would suggest that the anxiolytic-like effects of propranolol might prove to be limited either to a brief period after administration or to situations or patients in which the level of anxiety is not great.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…This has not been described clinically, although there have been reports that propranolol can produce depression (Hayes and Schulz, 1987). Nevertheless, the different explanations proposed for the present results would suggest that the anxiolytic-like effects of propranolol might prove to be limited either to a brief period after administration or to situations or patients in which the level of anxiety is not great.…”
Section: Discussioncontrasting
confidence: 60%
“…It has recently been argued that this family of drugs is of little value in anxiety (Noyes et al, 1981;Hayes andSchulz, 1983, 1987). Nevertheless, there remain isolated reports that they have been effective treatments for chronic (Kathol et al, 1980;Chaturvedi, 1985), acute (Neftel et al, 1982) or experimentally induced (Erdman et al, 1984) anxiety.…”
Section: Introductionmentioning
confidence: 98%
“…Despite these findings, Hayes and Schulz [1987] con cluded in their extensive review on beta-blockers in anx iety disorders that the research findings do not support the routine use of beta-blockers in clinical treatment. This is an important conclusion, since it means that the use of beta-blockers is still 'research issue', with no apparent clinical routine consequences.…”
Section: Pharmacology Of Phobiasmentioning
confidence: 98%
“…Although it has been suggested that ß-adrenoceptorantagonists may have a role in the treatment of social phobia, recent studies have been rather disappointing (Marshall et al, 1993). There is no systematic evidence that ß-adrenoceptor antagonists are useful in the treatment of other anxiety disorders such as panic disorder (Hayes & Schulz, 1987), although many patients receive them from general practitioners.…”
Section: Other Drugsmentioning
confidence: 99%